Fundamentals of aquacultural engineering - Lawson, Thomas B. (Chapman & Hall, 1995)
This essential volume offers the most up-to-date and comprehensive information on aquaculture engineering available, compiling basic engineering information for aquaculture facilities in a single resource. It will enable the reader to design and operate aquaculture facilities that meet the needs of an increasing, yet competitive market for cultivated seafood products.